Assessment of the gymnastics coaching and educational development program - Puja Sri Syahfitri; Padli, Padli; Sri Gusti Handayani; Nuridin Widya Pranoto (Jurnal Konseling dan Pendidikan, 2025)
This study aims to evaluate the effectiveness of the gymnastics coaching program in Pekanbaru City using the CIPP (Context, Input, Process, Product) evaluation model. Employing a qualitative descriptive approach, data were collected through interviews, observations, and documentation. Informants selected via purposive sampling included KONI officials, coaches, and athletes. Data were analyzed using triangulation to ensure validity.The findings reveal that while the program aligns with local sports policies and continues to operate, several critical challenges hinder its sustainability. In the context dimension, the program lacks long-term strategic planning and regular competition opportunities. From the input perspective, issues include outdated training facilities, insufficient funding, and weak coach regeneration. The process evaluation indicates the absence of systematic performance monitoring and limited coordination among key institutions. Lastly, the product dimension shows that although some athletes have achieved success, the lack of structured regeneration systems jeopardizes long-term outcomes.These results suggest the need for strategic improvements, including increased funding, upgraded infrastructure, structured talent development, and enhanced institutional collaboration. The study contributes a comprehensive, model-based evaluation framework that can inform future efforts in regional sports program development across Indonesia.